2013
DOI: 10.1007/s11589-013-0022-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic constraints on the spatial distribution of seismic activity

Abstract: The lithospheric magnetic field (LMF) in China and its surrounding are calculated using the spherical harmonic coefficients given by the NGDC-720 model. The LMF comes from the magnetization of minerals in the crust and in the uppermost mantle. It may, therefore, provide unique insight into lithospheric tectonic processes and mechanisms. Here, we study the geomagnetic manifestation of active tectonic blocks, and find a close correlation between the LMF and seismicity. Many large faults are found to closely over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…B z at this altitude reflects well not only the seismicity, but also the topography (see Additional file 1: Figure S2). The statistical result is similar to our previous visual inspection (Jiao et al 2013), while more accurate.…”
Section: Seismicity and The Gradient Of B Zsupporting
confidence: 87%
See 2 more Smart Citations
“…B z at this altitude reflects well not only the seismicity, but also the topography (see Additional file 1: Figure S2). The statistical result is similar to our previous visual inspection (Jiao et al 2013), while more accurate.…”
Section: Seismicity and The Gradient Of B Zsupporting
confidence: 87%
“…To study the distribution of magnetic anomalies with different horizontal wavelengths, we may select different ranges of degree n, as did Kang et al (2012). Since anomalies with different wavelengths have different attenuating characters, an alternative would be to select a different r. In a former study (Jiao et al 2013), we visually compared seismicity to magnetic anomalies at altitudes (H = 0 km, 50 km, 100 km, 200 km and 400 km). We found that B z at 200 km is mostly associated with seismicity.…”
Section: The Lmf Model and Active Tectonicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rajaram et al, 2009). Furthermore, the B z at an altitude of 200 km well delineates the geological characteristics such as faults and basins, and exhibits a better correlation with seismicity than the other two components (Jiao et al, 2013;Lei et al, 2018). Hence, the B z calculated at an altitude of 200 km from the EMM2017 model is used (the effects of the other two components are discussed in Supplementary Information) to invert the CPD.…”
Section: Datamentioning
confidence: 99%